Concreting works for beam and column at proposed two storey market in Tanjong Malim / Nor Afidah Ja’afar - Ja’afar, Nor Afidah (Universiti Teknologi Mara, Perak, 2014)
Majlis Daerah Tanjong Malim (MDTM) was build at 1 December 1979. It was located at peti surat 59, Bandar behrang 2020, 35900 TANJUNG MALIM PERAK DARUL RIDZUAN. MDTM was holding a few places such as at Bandar Tanjong Malim, Pekan Slim River, Pekan Behrang Ulu/Behrang Stesen, Pekan Slim Village and Pekan Trolak. The area of that site was around 10,410 hectare and the wide was 2160 hectare. MDTM just hold only cities and villages around Tanjong Malim. It had a few buildings that can give their income from sales and rents. They will take rents each building for every month. The functions of MDTM are to give cleaner services and attraction in operation area of MDTM, to manage budget and outcome accordance accurate and accountability, plan and escort the area of building follow by structure plan and planning plan and implement the laws with legal and exact.